Particle Size Determination of Mirtazapine - Mangaonkar, Kiran; Desai, Pulkeshi; Patil, Dhanaji (Asian Journal of Chemistry, 2012)
A simple, fast and accurate particle size determination method has been developed for the mirtazapine. Mirtazapine is an anti-depressant drug. The reproducible values of analysis results indicate high precision of the method. The average recovery and reproducibility of the method was found to be satisfactory.